Concrete abstract : exploring tactility in abstract animations from early avant-garde films to contemporary artworks - Siray, Basak Kaptan (2022)
After witnessing social chaos and the collapse of values at the beginning of the twentieth century, avant-garde artists insert new thought patterns and progressive aesthetic into the traditional perception of art. Being enthralled by the new film medium, former painters like Viking Eggeling, Walther Ruttman and Hans Richter start to experiment with light in two-dimensional film formats, they animate lines, stripes, basic shapes, play with the foreground and the background, and, most important of all, they construct a temporality within the visual order of the screen. Viking Eggeling’s Symphonie Diagonale (1921-24), Walther Ruttman’s Opus I (1921) and Hans Richter’s Rhythmus 21 (1921) show such temporality built in, which is caught by the idea of music as their titles suggest. These short abstract animation films attempt to discover the artistic possibilities of the new developing medium, film. Like the pioneer avant-garde abstract filmmakers, today’s artists still seek to stimulate a new perception for a possible embodiment that will activate the sense of touch in the audience. Tactility, enhanced by the material, opens up a new network of spatio-temporal relationships in the viewer’s consciousness and subjecthood. This essay aims to bring a historical perspective to the abstract moving images of which the tactile or haptic experience is a defining characteristic. Through a selection of abstract animations, the materiality of the film image and the screening site will be elaborated upon according to the haptic features that are corporally embodied by the viewers. In the light of historical abstract animation, the aim is to dwell upon the dynamics of a continuous tendency to capture tactile instances to help bring forth the spatial resonances as well as visualize and reedify the rhythmic passing of time.